Between Nomos and Physis: The Multiformity of the Sophists’s Speech - Eustacchi, Francesca (ΠΗΓΗ/FONS, 2022)
Sophists deal with the problem of relationship between nomos and physis in terms not only of opposition between, but also of intertwinement. On the one side, the discussion leads to an exaltation of the physis, with opposite effects: in some sophists (Hippias and Antiphon) nature warrants the equality among human beings, while, in other sophists (Callicles and Thrasymachus), nature becomes the basis for legitimizing the dominance of the strongest over the weakest. In this context, the nomos is considered an invention of the weakest to inhibit the strongest. On the other side, we find sophists (like Gorgias) that affirm the need to decide to follow the nomos or the physis on the basis of situation, that is to avoid unilateral positions, or sophists (like Anonymous of Iamblichus) that assume a “conciliatory” perspective between nomos and physis. Socrates completes the variety of this debate. In Criton, Socrates applies a manifold movement to the nomos, divine and human, thus deserving respect and, at the same time, modifiable.
Keywords: nomos; physis; sophists; Socrates; justice; immoralism